2019
DOI: 10.2217/bmm-2018-0401
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Marker Based on Risk Stratification with Prognostic Nutritional Index and Age for Nasopharyngeal Carcinoma Patients Who Received Neoadjuvant Chemotherapy

Abstract: Aim: To evaluate the prognostic value of pretreatment prognostic nutritional index (PNI) in nasopharyngeal carcinoma (NPC) patients treated with neoadjuvant chemotherapy followed by concurrent chemoradiotherapy. Materials & methods: We conducted a retrospective study on prognostic value of PNI in NPC patients. A new prognostic marker was explored based on risk stratification with PNI and age. Results: PNI and age were two independent prognostic factors for overall survival (OS) and progression free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Interestingly, this was because the conditional risk of recurrence or death for the older group (initially poorer prognosis) reduced less than that for the younger group (initially better prognosis), which was opposite to other factors. A possible reason was that older patients might experience a higher prolonged risk of recurrence or death due to increased comorbidity burdens, decreased performance status, and reduced tolerance to treatments [17,42–45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this was because the conditional risk of recurrence or death for the older group (initially poorer prognosis) reduced less than that for the younger group (initially better prognosis), which was opposite to other factors. A possible reason was that older patients might experience a higher prolonged risk of recurrence or death due to increased comorbidity burdens, decreased performance status, and reduced tolerance to treatments [17,42–45].…”
Section: Resultsmentioning
confidence: 99%
“…For example, if a patient with an age of <45 years has not experienced recurrence and on follow-up is found to be disease-free, his 3-year conditional risk for having disease failure after 5 years from diagnosis would be 4.5%, while the traditional the older group (initially poorer prognosis) reduced less than that for the younger group (initially better prognosis), which was opposite to other factors. A possible reason was that older patients might experience a higher prolonged risk of recurrence or death due to increased comorbidity burdens, decreased performance status, and reduced tolerance to treatments [17,[42][43][44][45].…”
Section: F I G U R Ementioning
confidence: 99%
“…[20,21]. PNI has been used as a predictive nutritional marker in patients with various diseases, such as malignancy [22], acute or chronic HF [23,24], heart failure with preserved ejection fraction (HFpEF) [25], pulmonary embolism (PE) [26], stable coronary artery disease (CAD) [27] and ST segment elevation myocardial infarction (STEMI) [28].…”
Section: Resultsmentioning
confidence: 99%
“…Several biomarkers, particularly B-type natriuretic peptide (BNP) [16], increased circulating inflammatory markers such as TNF-α [7,8], IL-6 [17], MCP-1 [18], NLR [9] and MHR [6] [20,21]. PNI has been used as a predictive nutritional marker in patients with various diseases, such as malignancy [22], acute or chronic HF [23,24], heart failure with preserved ejection fraction (HFpEF) [25], pulmonary embolism (PE) [26], stable coronary artery disease (CAD) [27] and ST segment elevation myocardial infarction (STEMI) [28]. The clinical significance of nutritional risk assessment in patients with HCM has not been well established.…”
Section: Resultsmentioning
confidence: 99%
“…Wei et al (21) and Topkan et al (22) also revealed PNI is independent prognostic factors for OS in metastatic NPC patients. Followed by He et al (23), a total of 377 newly diagnosed NPC patients treated with neoadjuvant chemotherapy plus CCRT at the Sichuan Cancer Hospital were reviewed, and revealed that the novel prognosis index PNI was related to OS (P<0.001)and PFS (P=0.008) for metastatic NPC patients. Furthermore, 539 patients with newly diagnosed non-metastatic NPC treated by CCRT were retrospectively analyzed by Miao et al (24) and demonstrated that the 5-year LRFS, DMFS, DSS, and OS of PNI ≤52.0 group were significantly worse than the PNI >52.0 group.…”
Section: Discussionmentioning
confidence: 99%